Provider readiness and implementation barriers for lung cancer screening in a safety-net system - Maria C. Mejia; Yu-Heng Hilary Ma; Lisa M. Lowenstein; Kiara K. Spooner; Gabrielle Duhon; Elisa E. Douglas; Viola Leal; Robert J. Volk (Preventive Medicine Reports)
Objective: Lung cancer screening (LCS) with low-dose computed tomography is a critical preventive strategy, yet implementation remains complex, particularly in safety-net settings. This study assessed provider knowledge, attitudes, and readiness to implement LCS, including shared decision-making (SDM) and smoking cessation, within a large urban safety-net healthcare system. Methods: A cross-sectional survey was distributed between February and September 2023 to 200 healthcare providers, including physicians, nurses, advanced practice providers, trainees, and administrators in Houston, Texas. The 26-item instrument assessed familiarity with Centers for Medicare & Medicaid Services (CMS) LCS coverage, SDM billing, role preferences in LCS implementation, support needs, and readiness to engage in related activities. Results: Seventy-four providers responded (37 % response rate), and 60 completed the survey. Most were physicians (63 %), with specialties in family (45 %) and pulmonary medicine (20 %). While 77 % were familiar with CMS coverage, only 50 % were aware of SDM visit reimbursement, and 15 % knew the billing codes. Most identified physicians as key to SDM (96.7 %) and smoking cessation (93.3 %). Providers prioritized support in eligibility guidance (67 %), insurance coverage (60 %), decision aids (58 %), and cessation training (42 %). Preferred decision aids included exam room videos (70 %), waiting room videos (65 %), brochures (62 %), and electronic record-integrated tools (50 %). Most believed LCS benefits outweighed risks (92 %) and reported high readiness to engage in screening. Conclusions: Providers in safety-net settings support LCS implementation but report critical gaps in knowledge and infrastructure. Addressing these barriers through multidisciplinary collaboration, provider training, and improved decision support can enhance equitable delivery of lung cancer screening.